Use of near-infrared spectroscopy in the neonatal intensive care unit (2012)
Near-infrared spectroscopy was first described in 1977 as a non-invasive technique to measure the cerebral oxygenation and cytochrome oxydase. Different techniques have been developed resulting in new instruments that make it possible to measure cerebral oxygenation in a non-invasive way. In this chapter the physiology and pathophysiology in relation to the measurement of cerebral oxygenation are explained and the direct possible clinical use enlightened, with special focus on measurement of ischemic cerebral hypoxia. The measurement of other organs like the liver, the bowel and the peripheral circulation are described. At the end, a short overview of future possible bed-side measurements like functional near-infrared spectroscopy, near-infrared imaging and photoacoustic measurements are given.